Catalytic Thiourea Promoted Electrophilic Thiocyanation of Indoles and Aromatic Amines with NCS/NH4SCN. Issue 11 (24th October 2016) - Wang, Cancan; Wang, Zhonghao; Wang, Liang; Chen, Qun; He, Mingyang
Abstract: A simple and efficient protocol for the electrophilic thiocyanation of indoles and aromatic amines with thiourea/NCS/NH4 SCN system has been developed. The major features of the present procedure are the mild conditions, good yields, short reaction times, and the use of inexpensive and readily available organocatalyst. Moreover, N ‐chlorosuccinimide (NCS) was found to be indispensable, and thiourea could greatly promote the reaction. Abstract : A simple and efficient protocol for the electrophilic thiocyanation of indoles and aromatic amines with thiourea/NCS/NH4 SCN system has been developed.